Effect of sterilization on the degree of esterification, FTIR analysis, and antibacterial activity of durian-rind pectin - Rahmawati, Inas Suci; Kusumaningrum, Harsi Dewantari; Yuliana, Nancy Dewi (Universiti Kebangsaan Malaysia, 2022)
Pectin is a common food ingredient used as a rheology modifier and recently recognized as an emerging bioactive compound. Degree of esterification (DE) and molecular weight (MW) are important determinants of its bioactivity. This study evaluated the effect of moist heat sterilization (121 °C, 15 min) on pectin from Indonesian durian rind as an alternative method to modify pectin. Sterilized pectin was compared in terms of DE, Fourier transform infrared (FTIR) analysis, gel-forming ability, and antibacterial activity to non-sterilized pectin and standard citrus-peel pectin. Durian-rind pectin was identified as a low-methoxyl pectin with DE of 26.50% and weak antibacterial activity. After sterilization, the DE and pH decreased. It lost the ability to form a gel which indicated pectin was degraded to lower molecules. Loss of bands at 1760-1745 cm-1 indicated that pectin underwent ester hydrolysis and generated free carboxyl groups. On the other hand, the sterilized durian-rind pectin showed strong antibacterial activity towards Staphylococcus aureus and Escherichia coli, with a reduction of 5 log cycles and 3 log cycles, respectively (with the initial bacterial level of 5 log cfu/mL). These results indicated that depolymerization and deesterification of pectin by heat sterilization was able to improve the antibacterial activity of durian-rind pectin.